THE ACUTE EFFECTS OF PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION(PNF) STRETCHING ON DYNAMIC BALANCE PERFORMANCE IN ELITE WRESTLERS - Ali Tatlıcı; Gürcan Ünlü (ümit doğan üstün, 2019)
The aim of this study was to investigate the effect of Proprioceptive Neuromuscular Facilitation (PNF) stretch techniques on dynamic standing balance performances using Biodex Balance System (BBS). Seven wrestlers from the Turkish National Team between the ages of 18 and 25 were tested before and immediately after PNF stretching interventions. The stretching protocol involved a 5-min warm-up at at at 70 rpm with 1-kp resistance on a stationary cycle ergometer followed by four PNF stretching exercises to stretch the leg extensor muscles of the dominant and nondominant limbs according to the procedures of a previous study. Balance was measured in two conditions; dominant and nondominant limbs over a period of 20s and Medial-lateral stability index (MLSI), Anterior-posterior stability index (APSI) and an Overall stability index (OSI) were recorded before and after PNF interventions. One way repeated-measures analysis of variance (ANOVA) was used to analyze the differences between pretest and posttest BBS values. There were no significant balance index differences after the PNF interventions for dominant leg (p>0.05). However, a significant increase was found in MLSI values for non-dominant leg. Even though the PNF stretching intervention reduced MLSI dynamic balance performance for the non-dominant leg in our findings, other BBS index scores showed that dynamic balance performance was not affected by the acute bout of PNF stretching.